High-stability aluminum foil for battery and preparation process of high-stability aluminum foil

By optimizing the alloy composition and preparation process of aluminum foil, aluminium foil with high mechanical strength, corrosion resistance and electrochemical stability is formed, which solves the problems of energy loss and life reduction in traditional aluminum foils in battery applications, and significantly extends the service life of the battery.

CN119776684APending Publication Date: 2025-04-08INNER MONGOLIA LIANSHENG NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411723466.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the production process, traditional battery aluminum foil has problems such as uneven grain structure, surface defects and insufficient corrosion resistance, which leads to a decrease in energy loss and life of the battery during charging and discharging, making it difficult to meet the development needs of high-performance batteries.

Method used

A high-stability aluminum foil preparation process is adopted, including alloy smelting, casting and rolling, cold rolling and intermediate annealing, surface treatment and heat treatment. By optimizing alloy composition and process parameters, aluminum foils with high mechanical strength, corrosion resistance and electrochemical stability are formed.

Benefits of technology

This process significantly improves the mechanical strength, corrosion resistance and electrochemical stability of aluminum foil, allowing it to withstand higher working pressures and electrochemical reactions during the battery use, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158639890000071
    Figure BDA0005158639890000071
Patent Text Reader

Abstract

The invention relates to a high-stability aluminum foil for a battery and a preparation process of the high-stability aluminum foil. The preparation process comprises the following steps: S1, alloy smelting: heating a high-purity aluminum ingot to 740-760 DEG C until the high-purity aluminum ingot is completely molten; magnesium, manganese, silicon and titanium alloy materials are added according to the mass percent; s2, cast rolling forming; s3, cold rolling and intermediate annealing are conducted, specifically, the aluminum plate is subjected to multiple times of cold rolling, and the final thickness is controlled to range from 15 micrometers to 25 micrometers; the intermediate annealing temperature is 320-350 DEG C, and the heat preservation time is 2 hours; s4, surface treatment is conducted, specifically, the surface of the aluminum foil is subjected to polishing treatment and then subjected to chemical oxidation, finally, a functional coating is coated, and the functional coating is a composition of one or more of aluminum oxide, silicon dioxide or titanium oxide; and S5, heat treatment is conducted, specifically, the aluminum foil is annealed for 3 hours in a vacuum furnace, and the cooling rate is 5-10 DEG C / min. According to the preparation process, the mechanical strength, corrosion resistance, conductivity and electrochemical stability of the aluminum foil can be effectively improved, the requirements of high-performance batteries are met, and the aluminum foil is particularly suitable for energy storage equipment such as lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation process of an aluminum foil, and more specifically to a high-stability aluminum foil for a battery and a preparation process thereof. Background Art

[0002] With the rapid development of the new energy industry, lithium-ion batteries have become an important energy storage device widely used in electric vehicles, energy storage equipment and consumer electronic products. As an important component of lithium-ion batteries, battery aluminum foil is widely used in electrode current collector materials due to its light weight, high conductivity and good processing performance. However, during the production process of traditional battery aluminum foil, due to uneven grain structure, surface defects and insufficient corrosion resistance, it is very easy to cause energy loss and reduced life of the battery during charging and discharging, making it difficult to meet the development needs of high-performance batteries.

[0003] Although the existing technology has made certain progress in the above-mentioned fields, there are still some problems that need to be solved. For example, traditional aluminum foil is prone to problems such as grain coarsening, uneven surface coating, and insufficient corrosion resistance during processing. In addition, the uniformity and adhesion of the surface oxide film and functional coating have an important influence on the durability of aluminum foil, but it is difficult for the existing process to take these performance indicators into account at the same time. Therefore, the development of a preparation process for high-stability aluminum foil for batteries with stable process and excellent performance has important technical value and application prospects. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, a high-stability aluminum foil for batteries and a preparation process thereof are provided. The specific scheme is as follows:

[0005] A preparation process of a high-stability aluminum foil for a battery, the preparation process comprising the following steps:

[0006] S1. Alloy smelting: heat the high-purity aluminum ingot to 740-760℃ and completely melt it; add magnesium, manganese, silicon and titanium alloy materials according to mass percentage, stir for 10-15 minutes to ensure uniform distribution; perform refining treatment under argon or nitrogen protection at a temperature of 730-740℃;

[0007] S2, casting and rolling forming: the smelted aluminum alloy liquid is quickly cooled by a casting and rolling mill, and the casting and rolling speed is 0.5-1.0 m / min to obtain an aluminum alloy plate with a preliminary thickness of 6-10 mm;

[0008] S3, cold rolling and intermediate annealing: the aluminum plate is cold rolled for multiple times, and the final thickness is controlled at 15-25 μm; the intermediate annealing temperature is 320-350°C, and the holding time is 2 hours;

[0009] S4, surface treatment: polishing the surface of the aluminum foil, chemically oxidizing it, and finally coating it with a functional coating, wherein the functional coating is a combination of one or more of aluminum oxide, silicon dioxide or titanium oxide;

[0010] S5. Heat treatment: anneal the aluminum foil in a vacuum furnace for 3 hours at a cooling rate of 5 to 10°C / min.

[0011] Furthermore, after smelting, S1 is subjected to a refining treatment, using a chloride salt refining agent, with the temperature controlled at 730-740° C. and the refining time being 20 minutes.

[0012] Furthermore, the S4 surface treatment also includes the following sub-steps:

[0013] S401: Mechanically polishing or electrolytically polishing the surface of the aluminum foil;

[0014] S402: then chemical oxidation treatment is performed, in which the aluminum foil is immersed in an oxidation solution containing 5% nitric acid and 2% phosphoric acid for 2 to 5 minutes to form a dense oxide film with a thickness of 50 to 100 nm, which significantly improves the corrosion resistance and electrochemical stability of the aluminum foil;

[0015] S403: coating the surface of the aluminum foil with a functional coating having a thickness of 2 to 5 μm, and performing a heat curing treatment at 150 to 180° C. for 15 minutes.

[0016] Furthermore, the annealing temperature during the S5 heat treatment is 400-450°C.

[0017] Furthermore, the number of cycles of cold rolling and annealing in S3 is 3 to 5 times.

[0018] Furthermore, the thickness of the chemical oxidation film is 50-100 nm.

[0019] Furthermore, the grain size of the aluminum foil is controlled to be 3-5 μm by final annealing.

[0020] The aluminum alloy obtained according to the above preparation process, the aluminum foil comprises the following alloy components: Mg 0.5-1%; Mn 0.2-0.5%; Si 0.05-0.2%; Ti 0.01-0.05%; the balance is Al.

[0021] Beneficial effects:

[0022] The present invention provides a high-stability aluminum foil for batteries and a preparation process thereof, which has the following significant beneficial effects by optimizing multiple links such as alloy composition, casting and rolling forming, cold rolling and intermediate annealing, surface treatment and heat treatment:

[0023] (1) The alloying treatment not only improves the mechanical strength and corrosion resistance of the aluminum foil, but also improves the plasticity and processing properties of the aluminum foil, enabling it to withstand higher working pressure and electrochemical reactions during battery use, thereby extending the battery life.

[0024] (2) During the multiple cold rolling and intermediate annealing processes, the grain size of the aluminum foil is ultimately controlled within the range of 3 to 5 μm by precisely controlling the number of cold rolling times, annealing temperature, and holding time, thereby effectively reducing the grain boundary defects in the aluminum foil, improving the surface quality and internal structure of the aluminum foil, and improving its mechanical properties and stability.

[0025] (3) The present invention uses chemical oxidation treatment to generate a dense oxide film with a thickness of 50 to 100 nm, which can significantly improve the corrosion resistance of the aluminum foil. At the same time, the surface coating of the functional coating further enhances the electrochemical stability of the aluminum foil, effectively preventing oxidation and corrosion of the aluminum foil surface during long-term use of the battery.

[0026] (4) During the casting and rolling process, the thickness uniformity and surface flatness of the aluminum alloy sheet are ensured by controlling the casting and rolling speed and the stability of the casting and rolling process, laying the foundation for the subsequent cold rolling and annealing process. Multiple cold rolling and intermediate annealing treatments help improve the stability of the aluminum foil and ensure the consistency and high quality of the product. DETAILED DESCRIPTION

[0027] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0028] Example 1

[0029] S1. Alloy smelting:

[0030] The high purity aluminum ingot is heated to 750℃ and completely melted.

[0031] 0.8% magnesium (Mg), 0.3% manganese (Mn), 0.1% silicon (Si), and 0.03% titanium (Ti) were added by mass percentage and stirred for 12 minutes to ensure that the alloy components were evenly distributed.

[0032] Under argon protection, the refining treatment was carried out, the temperature was controlled at 735°C, and the refining time was 20 minutes.

[0033] S2, Casting and Rolling:

[0034] The smelted aluminum alloy liquid is quickly cooled by a casting and rolling mill, and the casting and rolling speed is controlled at 0.8 m / min to obtain an aluminum alloy sheet with an initial thickness of 8 mm.

[0035] S3, cold rolling and intermediate annealing:

[0036] The aluminum alloy sheet was cold rolled four times, and intermediate annealing was performed after each cold rolling.

[0037] The final thickness of the aluminum foil is controlled at 20 μm.

[0038] The intermediate annealing temperature is 330°C and the holding time is 2 hours.

[0039] The annealing process uses a holding tank to control the temperature and ensure uniform heating.

[0040] S4. Surface treatment

[0041] The surface of the aluminum foil is first electropolished to improve surface smoothness and uniformity.

[0042] Then, chemical oxidation was performed by immersing the aluminum foil in an oxidation solution containing 5% nitric acid and 2% phosphoric acid for 3 minutes to generate a dense oxide film with a thickness of 60 nm.

[0043] The functional coating was applied to the surface of the aluminum foil with a coating thickness of 3 μm, and after coating, a heat curing treatment was performed at 160° C. for 15 minutes.

[0044] S5. Heat treatment:

[0045] Place the aluminum foil in a vacuum furnace, set the temperature to 420 °C, and anneal for 3 h.

[0046] The cooling rate was controlled at 7 °C / min to optimize the grain structure and improve the stability of the aluminum foil.

[0047] Example 2

[0048] S1. Alloy smelting:

[0049] The high purity aluminum ingot is heated to 755℃ and completely melted.

[0050] Add 0.6% magnesium (Mg), 0.4% manganese (Mn), 0.15% silicon (Si), and 0.02% titanium (Ti) by mass percentage and stir for 10 minutes to ensure uniform distribution.

[0051] Under nitrogen protection, the refining temperature was controlled at 740°C and the refining time was 20 minutes.

[0052] S2, Casting and Rolling:

[0053] The smelted aluminum alloy liquid was quickly cooled by a casting and rolling mill, and the casting and rolling speed was controlled at 0.6 m / min to obtain an aluminum alloy sheet with an initial thickness of 6.5 mm.

[0054] S3, cold rolling and intermediate annealing:

[0055] The aluminum alloy sheet was cold rolled for 5 times, and intermediate annealing was performed after each cold rolling.

[0056] The final thickness of the aluminum foil is controlled at 18 μm.

[0057] The intermediate annealing temperature is 340°C and the holding time is 2 hours.

[0058] The annealing process uses an atmosphere furnace to ensure temperature stability and uniform heating of the aluminum foil.

[0059] S4. Surface treatment:

[0060] The surface of the aluminum foil is first mechanically polished to improve surface smoothness and remove surface oxides.

[0061] Then, chemical oxidation was performed by immersing the aluminum foil in an oxidation solution containing 5% nitric acid and 2% phosphoric acid for 4 minutes to generate a dense oxide film with a thickness of 80 nm.

[0062] The functional coating was applied to the surface of the aluminum foil with a coating thickness of 2.5 μm, and after coating, a heat curing treatment was performed at 170° C. for 16 minutes.

[0063] S5. Heat treatment:

[0064] Place the aluminum foil in a vacuum furnace, set the temperature to 430 °C, and anneal for 3 h.

[0065] The cooling rate was controlled at 6 °C / min to optimize the grain structure and improve the stability of the aluminum foil.

[0066] Example 3

[0067] S1. Alloy smelting:

[0068] The high purity aluminum ingot is heated to 740℃ and completely melted.

[0069] Add 0.9% magnesium (Mg), 0.2% manganese (Mn), 0.1% silicon (Si), and 0.03% titanium (Ti) by mass percentage and stir for 15 minutes to ensure uniform distribution.

[0070] Under argon protection, the refining temperature was controlled at 730°C and the refining time was 20 minutes.

[0071] S2, Casting and Rolling:

[0072] The smelted aluminum alloy liquid was quickly cooled by a casting and rolling mill, and the casting and rolling speed was controlled at 0.9 m / min to obtain an aluminum alloy sheet with an initial thickness of 9 mm.

[0073] S3, cold rolling and intermediate annealing:

[0074] The aluminum alloy sheet is cold rolled three times, and intermediate annealing is performed after each cold rolling.

[0075] The final thickness of the aluminum foil is controlled at 22 μm.

[0076] The intermediate annealing temperature is 325°C and the holding time is 2 hours.

[0077] The annealing process uses an atmosphere furnace to ensure uniform heating and stable temperature control of the aluminum foil.

[0078] S4. Surface treatment:

[0079] The surface of the aluminum foil is first electropolished to improve surface smoothness and uniformity.

[0080] Then, chemical oxidation was carried out by immersing the aluminum foil in an oxidation solution containing 5% nitric acid and 2% phosphoric acid for 5 minutes to generate a dense oxide film with a thickness of 70 nm.

[0081] The functional coating was coated on the surface of the aluminum foil with a coating thickness of 3 μm, and after coating, a heat curing treatment was performed at 150° C. for 18 minutes.

[0082] S5. Heat treatment:

[0083] Place the aluminum foil in a vacuum furnace, set the temperature to 440 °C, and anneal for 3 h.

[0084] The cooling rate was controlled at 8 °C / min to optimize the grain structure and improve the stability of the aluminum foil.

[0085] The performance of the aluminum foils of Examples 1 to 3 was tested, and the test data are as follows:

[0086]

[0087]

[0088] It can be seen from the above table that the aluminum foil obtained in this embodiment has enhanced tensile strength, elongation, electrical conductivity and corrosion resistance.

[0089] As a further improvement, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A process for preparing a high-stability aluminum foil for a battery, characterized in that: The preparation process comprises the following steps: S1. Alloy smelting: heat the high-purity aluminum ingot to 740-760℃ and completely melt it; add magnesium, manganese, silicon and titanium alloy materials according to mass percentage, stir for 10-15 minutes to ensure uniform distribution; perform refining treatment under argon or nitrogen protection at a temperature of 730-740℃; S2, casting and rolling forming: the smelted aluminum alloy liquid is quickly cooled by a casting and rolling mill, and the casting and rolling speed is 0.5-1.0 m / min to obtain an aluminum alloy plate with a preliminary thickness of 6-10 mm; S3, cold rolling and intermediate annealing: the aluminum plate is cold rolled for multiple times, and the final thickness is controlled at 15-25 μm; the intermediate annealing temperature is 320-350°C, and the holding time is 2 hours; S4, surface treatment: polishing the surface of the aluminum foil, chemically oxidizing it, and finally coating it with a functional coating, wherein the functional coating is a combination of one or more of aluminum oxide, silicon dioxide or titanium oxide; S5. Heat treatment: anneal the aluminum foil in a vacuum furnace for 3 hours at a cooling rate of 5 to 10°C / min.

2. The process for preparing a high-stability aluminum foil for batteries according to claim 1, characterized in that: After smelting, S1 is refined using a chloride salt refining agent at a temperature of 730-740°C for 20 minutes.

3. The process for preparing a high-stability aluminum foil for batteries according to claim 1, characterized in that: S4 surface treatment also includes the following sub-steps: S401: Mechanically polishing or electrolytically polishing the surface of the aluminum foil; S402: then chemical oxidation treatment is performed, in which the aluminum foil is immersed in an oxidation solution containing 5% nitric acid and 2% phosphoric acid for 2 to 5 minutes to form a dense oxide film with a thickness of 50 to 100 nm, which significantly improves the corrosion resistance and electrochemical stability of the aluminum foil; S403: coating the surface of the aluminum foil with a functional coating having a thickness of 2 to 5 μm, and performing a heat curing treatment at 150 to 180° C. for 15 minutes.

4. The process for preparing a high-stability aluminum foil for batteries according to claim 1, characterized in that: The annealing temperature during the S5 heat treatment is 400-450°C.

5. The process for preparing a high-stability aluminum foil for batteries according to claim 1, characterized in that: The number of cycles of cold rolling and annealing in S3 is 3 to 5 times.

6. The process for preparing a high-stability aluminum foil for batteries according to claim 1, characterized in that: The thickness of the chemical oxidation film is 50-100 nm.

7. The process for preparing a high-stability aluminum foil for batteries according to claim 1, characterized in that: The grain size of the aluminum foil is controlled to 3 to 5 μm by final annealing.

8. The aluminum alloy obtained by the preparation process according to any one of claims 1 to 7, characterized in that: The aluminum foil comprises the following alloy components: Mg 0.5-1%, Mn 0.2-0.5%, Si 0.05-0.2%, Ti 0.01-0.05%, and the balance is Al.